Flavones as a Privileged Scaffold in Drug Discovery: Current Developments - Boniface, Pone K.; Elizabeth, Ferreira I. (Current Organic Synthesis, 2019)
Background: Flavones are one of the main subclasses of flavonoids with diverse pharmacological properties. They have been reported to possess antimalarial, antimicrobial, anti-tuberculosis, anti-allergic, antioxidant, anti-inflammatory activities, among others. Objective: The present review summarizes the recent information on the pharmacological properties of naturally occurring and synthetic flavones. Methods: Scientific publications referring to natural and synthetic flavones in relation to their biological activities were hand-searched in databases such as SciFinder, PubMed (National Library of Medicine), Science Direct, Wiley, ACS, SciELO, Springer, among others. Results: As per the literature, seventy-five natural flavones were predicted as active compounds with reference to their IC50 (<20 μg/mL) in in vitro studies. Also, synthetic flavones were found active against several diseases. Conclusion: As per the literature, flavones are important sources for the potential treatment of multifactorial diseases. However, efforts toward the development of flavone-based therapeutic agents are still needed. The appearance of new catalysts and chemical transformations is expected to provide avenues for the synthesis of unexplored flavones, leading to the discovery of flavones with new properties and biological activities.
Keywords: multifactorial diseases